Wastewater treatment : application of new functional materials - Chen, Jianyu; Luo, Jun; Luo, Qijin; Pang, Zhihua (China Environment Publishing Group ; Walter de Gruyter, 2018)
This book describes the research results and applications of functional zeolite, functional ceramsite, modified montmorillonite and other functional materials in water purification areas. With abundant project experiences, the book is an essential reference for researchers and PhD students in environmental science, material science, environmental chemistry, as well as industrial engineers.